Evaluation of Quality Public Transport Criteria in Terms of Passenger Satisfaction - Olivková Ivana (Transport and Telecommunication, 2016)
This article presents a detailed description and explanation of the methodology for evaluation of quality public transport criteria in terms of passenger satisfaction. In 2011-2014 this method was applied in an assessment of passenger satisfaction with the urban public transport system in Ostrava. In order to assess passengers’ satisfaction, traffic survey has been chosen utilizing questionnaire and student inquirers. The results achieved by application of the method have been processed to evaluate time accessibility criteria of a public transport system. Time accessibility criteria group (accessibility of stops, waiting for a connection and transferability in the public transport network) evaluates physical and psychological aspects of the passenger during his arrival at the station, while leaving the station, in the course of waiting for a connection and during the transfer. The time accessibility criteria are considered the most significant criteria that impact a passenger’s decision to utilise public transport options.